Clinical profile of premenopausal female patients with coronary artery disease - T. D., Unnikrishnan Kartha; N. R., Ambili; Mathew, Donna; B., Renymol (International Journal of Research in Medical Sciences, 2018)
Background: Coronary artery disease is becoming the leading cause of death in the world. The incidence of CAD in females has increased rapidly in the past decades. This study aimed to analyze the clinical profile of premenopausal women with CAD and elucidate on the possible risk factors. Methods: Premenopausal female patients admitted with an acute coronary syndrome as diagnosed by history, ECG and laboratory tests were recruited. Clinical and biochemical parameters were recorded. Results: Mean age of study participants was 41.6±8.18 yrs. Unstable angina (60%) was the most common clinical presentation. Proportion of women with various risk factors of CAD in our study population were as follows dyslipidemia (65%), family history of premature CAD (57.5%), hypertension (55%), diabetes mellitus (42.5%), hypothyroidism (40%), PAD (37.5%), CKD (35%) and SLE (20%). Most (95%) of the study population had high LDL-c. Three fourth (77.5%) of the study population had low HDL Approximately half of the study population had fatty liver on ultrasonography. Triglyceridemia was found in 72.5% of the study population. Conclusions: Premature CAD is increasingly evident in young premenopausal women in India. Premenopausal CAD in India is of multi factorial causation and dyslipidemia, hypertension, diabetes mellitus, central obesity and family history of premature CAD play a crucial role in its development.